ChemInform Abstract: Synthesis, Crystal Structure and Catalytic Activity of the Guanidinium Cation Directed Nickel(II)‐Containing Open Wells—Dawson 19‐Tungstodiarsenate(III) [{Ni(H2O)4}2{Na (H2O)}As2W19O67(H2O)] 9‐. Issue 25 (5th June 2015) - Saini, Mukesh Kumar; Gupta, Rakesh; Singh, Surendra; Hussain, Firasat
Abstract: The open Wells—Dawson type compound [C(NH2 )3 ]5 Na4 [{Ni(H2 O)4 }2 {Na(H2 O)} As2 W19 O67 (H2 O)] 9‐ ·22 H2 O is obtained from an aqueous mixture of NiCl2, Py‐2, 6‐CO2 H (80 °C, 1 h), and trilacunary Na9 [α‐AsW9 O33 ] which is added prior to guanidinium chloride at pH 5.8 as the structure directing cation (2‐3 weeks, 46% yield).